Research on livestock, livelihoods and innovation - Thorne, Peter J.; Conroy, C. (Elsevier, 2017)
In this chapter, we have surveyed some of the issues relating to the implementation of participatory research for livestock development. Participatory research is only one type of research paradigm, and we do not see it as a replacement for traditional research with a technological focus. However, it can often help to generate research outputs that are much more focused on the needs of end-users in the world’s least developed countries (LDCs). Many of the issues related to applying participatory research to livestock constraints and opportunities are similar to those for other household enterprises. There is, however, a number of unique features of the role that livestock play in households, such as their capacity to support other aspects of the farming system through the provision of draught power and high quality organic matter for soil amendment (manure/compost), as well as their contribution to rolling household incomes. In smallholder farm systems, livestock are normally highly integrated in the system, both deriving and conferring benefits on other enterprises within the system, and their contributions to livelihoods are diverse and not just related to the provision of food. Much has been made of the negative impacts of livestock on environmental parameters in recent years. While effective management of livestock is essential to mitigate against their potentially negative environmental effects, it can be argued that these have often been overstated, and that good livestock management can actively support good environmental outcomes. Livestock populations are likely to increase in LDCs over the coming decades, so well planned research is likely to continue to be very important in supporting this trend by identifying approaches for increasing the productive efficiency of livestock enterprises.